Formation of Character of Environmental Care Based on Local Wisdom in Surakarta - Wendy Librata; Dewi Gunawati Gunawati; Triyanto Triyanto (Budapest International Research and Critics University, 2019)
One of the problems regarding environmental damage is human's bad behavior towards the environment. This relates to the character or personality of humans who do not care about environmental sustainability. Environmental damage due to human behavior will bring adverse effects or threaten human survival. The method used in research uses a qualitative approach. As for the results of the research, first, the formation of environmentally friendly character based on local wisdom can be done through education in schools. The teacher provides education or teaching by taking Javanese cultural value related to preserving the environment. Family, through parents provides advice and messages relating to the formation of environmental care character by taking the values contained in local wisdom. Within the scope of the RT programs can be run that lead to environmental hygiene concerns as well as making slogans taken from ancestral advice that can encourage environmental care.